English Learning Courseware for Slow Learners - Yahya, Mohd Izzat Helmy (Universiti Teknologi PETRONAS, 2009)
The aim ofthis report is to present the idea of building a courseware for disabled students in primary school. The main purpose of doing this courseware is to create a new learning environment for disabled students. There are few types ofdisabled students and one ofthem is the slow learner. Slow learner is aterm that is sometimes used for low ability students, with IQ between 70 and 85.The target user for this courseware is the slow learner students in Sekolah Kebangsaan Pengkalan Pegoh(SKPP),Ipoh,Perak. There is one class for slow learner there which is Amanah class. This courseware will help the respective students to learn English. The content ofthe courseware will be based on the syllabus given by their English teacher. To build the courseware,I have used the prototyping methodology.Prototyping methodology is divided into 4phases which are planning,analysis,design and implementation. For planning and analysis phases, Ihave made some research through school visit to know the user well. Based on planning and analysis, I have decided to do the design and implementation phases according to 3levels which are pre-test,post test and the real courseware. These levels can help me to develop the courseware based on the user's demand. Each level will be sent to the user to be tested. The result from each phase will be discussed more detail in Result and Discussion section. As a conclusion, deep understanding of the user requirement is important to ensure that the courseware really help the slow learners to learn English. IV